2020
DOI: 10.1088/1361-648x/ab8c8a
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of volume and surface driven crystallization in thin films

Abstract: A mathematical model of the crystallization process in a thin film is presented with the purpose to overcome the limitations of Kolmogorov-Johnson-Mehl-Avrami theory regarding finite-size systems. Two ways of nucleation are taken into account: at the film boundaries and in the bulk. The solution is obtained in terms of crystallization probability, which is the probability of a point inside the film to be included in the crystal at a given moment of time. It is shown that the characteristic feature of crystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…This allows us to define the activation energy value E a via the approximation of the line slope in the semi-logarithmic scale. The calculated value of the activation energy for the initial sample is 0.41 ± 0.01 eV, which agrees with the previous data [ 39 ]. The activation energy for the conductivity in direction 1–1 orthogonal to the scanlines is 0.40 ± 0.01 eV and does not differ dramatically from the activation energy of the unirradiated sample.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This allows us to define the activation energy value E a via the approximation of the line slope in the semi-logarithmic scale. The calculated value of the activation energy for the initial sample is 0.41 ± 0.01 eV, which agrees with the previous data [ 39 ]. The activation energy for the conductivity in direction 1–1 orthogonal to the scanlines is 0.40 ± 0.01 eV and does not differ dramatically from the activation energy of the unirradiated sample.…”
Section: Resultssupporting
confidence: 91%
“…Thus, the observed Raman spectra transformation most likely indicates a transition from an amorphous to a face-centered cubic (fcc) crystalline structure [ 30 , 37 ] after laser treatment. The observed laser-induced crystallization of GST225 thin films can be described by the nucleation processes, with subsequent nanocrystal growth [ 38 , 39 ]. In particular, the forming nuclei may be needle-shaped crystal particles aligned along the applied laser field [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it might be assumed that the observed behavior is related to the appearance and increase of the crystalline fraction in GST225 [7]. The crystallization can be described by the simultaneous volume and surface nucleation processes [44]. In the case of Ns = 750, the Raman spectra showed that the intensity ratio of the 125 cm −1 line to the 110-200 cm −1 broadband maximum is smaller in the laser spot center than at the periphery area (Figure 4b).…”
Section: Structural Propertiesmentioning
confidence: 99%
“…Therefore, it might be assumed that the observed behavior is related to the appearance and increase of the crystalline fraction in GST225 [7]. The crystallization can be described by the simultaneous volume and surface nucleation processes [44].…”
Section: Structural Propertiesmentioning
confidence: 99%